Comprensión lectora en estudiantes de primero de secundaria del Callao con y sin trastorno por déficit de atención con hiperactividad - García Regalado, Graciela (2010)
This research attempted to compare the levels of reading comprehension in students with and without Attention-Deficit Hyperactivity Disorder (ADHD). The study is descriptive comparative, with a total sample of 44 students (22 with ADHD and 22 without ADHD) between men and women, aged between 12 and 14 years, first grade of secondary in three public educational institutions in Callao. We used the alignment of EDAH scale by Farré and Narbona (2000) to identify the sample and the Reading Comprehension test by Tapia (1982), both instruments adapted to Lima. The scores showed differences statistically significant in reading comprehension between these two groups, for students without ADHD, It means that students without ADHD showed higher levels of reading comprehension than the students affected by that disorder.